Discharge Plan for Mothers of Children Undergoing Congenital Heart Surgery - Doyle, Michael P; McKervey, M. Anthony (Journal of Biomedicine and Biochemistry, 2022)
Background: Congenital heart defect is the second cause of death in infancy and childhood and is the leading cause of childhood morbidity and mortality. Congenital heart surgery corrects a heart defect that a child is born with it. Aim: This study aimed at evaluating the effect of discharge plans for mothers and their children undergoing congenital heart surgery. setting: this study was conducted at the outpatient clinic of Cardio Vascular and Thoracic Academy Ain Shams University Hospitals. Sample: 70 mothers and their children undergoing congenital heart surgery were included in this study.Tools of data collection: two different tools were used. First tool: consists of interviewing questionnaire to asssocio-demographic his characteristics of mothers and their children, knowledge, reported practices of mothers for their children undergoing congenital heart surgery, Second tool: Assessment of child health status. Result: revealed that 81.4% of the studied mothers achieved poor knowledge scores in the pre-implementation phase, it improved to 92.9% of them achieved well in the post-implementation phase. Only 18.6% & 7.1% of them achieved average in both the pre-and post-implementation phase respectively and 91.4% of the study sample’s total mothers’ practice was unsatisfactory in the pre-implementation phase, but 97.1% of them were satisfactory in the post-implementation phase.Conclusion: there was a strong statistically significant correlation between the mother’s total knowledge and total reported practices score on the post-test (P